Preparation method and application of modified phenolic resin adhesive
By simulating the hardening mechanism of the lobster shell, the functionalized graphene of dopa grafted chitosan and polyethyleneimine were combined with phenolic resin to build a cross-linking and hybrid system, which solved the curing speed and toughness of phenolic resin adhesives. , realizes efficient preparation of modified phenolic resin adhesives.
Patent Information
- Application Number
- CN202411262767.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-20
AI Technical Summary
The curing temperature of existing phenolic resin adhesives is high and the curing speed is slow, which leads to problems such as stubble collapse and cracking of artificial boards. The existing toughening methods cannot simultaneously improve the curing speed and water resistance.
By simulating the hardening mechanism of the lobster shell, the functionalized graphene of dopa grafted chitosan and polyethyleneimine are combined with phenolic resin to construct a 'phenolic-amine' cross-linking and organic-inorganic hybrid system to achieve high toughness and Fast curing.
The phenolic resin adhesive with high toughness, strength and rapid curing is achieved, which solves the curing speed and toughness problems, and reduces the cost and pollution of the graphene modification process.
Smart Images

Figure CN119161838A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of wood resin adhesives, and specifically relates to a DOPA-grafted chitosan and polyethyleneimine functionalized graphene modified phenolic resin adhesive and a preparation method thereof. Background Art
[0002] my country's production of wood-based panels accounts for about 50% to 60% of the world's total production of wood-based panels, and its production has been increasing year by year, ranking first in the world's wood-based panel production all year round. Adhesives are the main raw materials for the production of wood-based panels. my country needs to consume more than 15 million tons of wood adhesives every year. Its development and progress are important guarantees for ensuring the performance indicators of wood-based panels. Phenolic resin adhesives have excellent water-resistant bonding properties, weather resistance, wear resistance and chemical corrosion resistance, and are widely used in the production of water-resistant and weather-resistant outdoor wood-based panels such as reconstituted wood / reconstituted bamboo. However, due to the low reactivity of phenol and formaldehyde, the curing temperature of phenolic resin is high and the curing speed is slow. In addition, at high curing temperatures, a dense cross-linked network is formed inside the phenolic resin, which hinders the movement of molecular chains and causes the adhesive to be brittle, which ultimately leads to the production of wood-based panels that are prone to collapse and cracking. Therefore, it is urgent to develop phenolic resins with enhanced toughness and fast curing.
[0003] In order to improve the toughness of phenolic resin, researchers used vegetable oil, rubber, and thermoplastic resin to modify phenolic resin, but the introduction of flexible molecular chains caused the strength and rigidity of the modified resin to decrease. The addition of inorganic substances such as montmorillonite, metal nanooxides, and graphene oxide can also improve the toughness of phenolic resin, but the toughening effect of these materials is poor, and they are easy to agglomerate in the resin matrix, resulting in stress concentration. In addition, these toughening methods cannot simultaneously improve the curing speed of phenolic resin. In order to increase the curing speed of phenolic resin, researchers used metal ions, curing agents, resorcinol, etc. to modify phenolic resin. Among them, resorcinol has the best effect on improving the curing speed, but the cost of the modified resin is significantly increased. The addition of condensed tannins, hydrolyzed tannins, urea, etc. can accelerate the curing of phenolic resin, but it will lead to a decrease in the water resistance and bonding strength of the modified resin. Therefore, it is urgent to seek new ideas to construct toughened, enhanced and fast-curing phenolic resins. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a phenolic resin adhesive with high toughness, high strength and rapid curing which is simple, convenient, green and environmentally friendly and has strong industrial feasibility.
[0005] Natural organisms provide new ideas for the development of toughened, reinforced and fast-curing phenolic resins. Natural lobster shells have excellent mechanical properties, with a Young's modulus of 1 to 20 GPa, a strength of 10 to 100 MPa, and a hardness of 200 to 400 MPa. In order to resist predators, during the process of molting, after the old shell is removed, the lobster's soft skin quickly hardens at room temperature to form a dark and hard skin. Studies have found that lobster shells are mainly composed of amino acid-rich compounds such as chitin and protein, inorganic mineral reinforcement materials such as calcium carbonate, dopamine and its derivatives. Dopamine and its derivatives are oxidized to quinone structures under the action of oxygen and polyphenol oxidase, and then cross-linked with amino-rich compounds. This "phenol-amine" chemical cross-linking and inorganic mineral reinforcement is the main mechanism of lobster epidermis hardening. Therefore, by simulating the hardening mechanism of lobster epidermis to construct "phenol-amine" cross-linking and inorganic mineral reinforcement in phenolic resin, it is expected to improve toughness and curing rate at the same time.
[0006] Inspired by the hardening process of lobster epidermis, this patent composites dopamine-grafted chitosan (DCS) and polyethyleneimine-modified graphene (PEI@G) with phenolic resin (PF), constructs a "phenol-amine" crosslinking and organic-inorganic hybrid system in the PF matrix, and prepares modified phenolic resin DCS / PG / PF. Dopamine hydrochloride (DOPA) is copolymerized with oxidized chitosan (CS) to prepare DCS with a comb-like structure. Polyethyleneimine (PEI) and graphite powder are prepared by simple and economical mixing and ball milling to prepare PEI@G. The preparation of PEI@G by the co-mixing ball milling method can solve the high cost of directly modifying phenolic resin with graphene and the pollution problem of the graphene modification process, and the modification of PEI can promote the uniform dispersion of graphene in the resin. At the same time, under the alkaline conditions inherent in PF resin, DOPA can be oxidized to an o-benzoquinone structure, thereby covalently crosslinking with the amino group in PEI, and finally realizing the preparation of a phenolic resin with high toughness, strength and fast curing speed.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a modified phenolic resin adhesive comprises the following steps:
[0009] (1) oxidized chitosan is reacted and grafted with dopamine to prepare dopamine-grafted chitosan, denoted as DCS;
[0010] (2) ball milling polyethyleneimine and graphite powder together to prepare polyethyleneimine functionalized graphene, denoted as PEI@G;
[0011] (3) The DOPA-grafted chitosan obtained in step (1) and the polyethyleneimine-functionalized graphene prepared in step (2) are blended with unmodified phenolic resin (PF) to prepare a modified phenolic resin adhesive (DCS / PG / PF).
[0012] Specifically, in step (1), the oxidized chitosan is prepared by dispersing chitosan and sodium periodate in water, adjusting the system to be acidic and reacting, and then washing the product after the reaction with water until it becomes colorless and drying it.
[0013] Preferably, the concentration of chitosan is 8-10wt%, preferably 4wt%, the mass ratio of chitosan to sodium periodate is 1:0.5-1:2, the pH of the reaction system is adjusted to 4.5-5.5 with hydrochloric acid, and the reaction system is placed in a dark environment at 50°C for 3-5 hours.
[0014] Preferably, in step (1), oxidized chitosan and dopamine are dissolved in ethanol in a mass ratio of 1:1 to 1:3, preferably 1:2, the reaction system is heated to 70 to 90°C for 48 to 72 hours, preferably 48 hours, the mixture after the reaction is dialyzed in water for 3 to 5 days, then rotary evaporated and freeze-dried to obtain dopamine-grafted chitosan DCS.
[0015] In step (2), graphite powder and polyethyleneimine are mixed in a mass ratio of 1:1 to 1:5 and ball-milled for 20 to 24 hours at a ball-milling speed of 500 to 800 rpm. The ball-milled sample is dispersed in water at a concentration of 10 to 20 mg / mL and ultrasonicated for 1 hour at an ultrasonic intensity of 400 to 500 W. The ultrasonicated dispersion is centrifuged at 3000 to 5000 rpm for 10 to 20 minutes, and the upper PEI@G aqueous dispersion is concentrated to a solid concentration of 50%, preferably concentrated to a solid concentration of 50% by rotary evaporation.
[0016] Step (3) The unmodified phenolic resin is prepared by mixing phenol and formaldehyde in a molar ratio of 1:2.2, and DOPA-grafted chitosan DCS and polyethyleneimine functionalized graphene PEI@G are mixed in a mass ratio of 1:1 and then added to the unmodified phenolic resin for blending. The added mass is 1-12%, and the mixture is stirred at room temperature for 20 minutes to prepare the modified phenolic resin DCS / PG / PF.
[0017] In one embodiment, the unmodified phenolic resin is prepared by mixing 50 g of phenol, 40 g of water, 25 g of sodium hydroxide solution (40 wt %) and 75 g of formaldehyde solution (36-37 wt %) in a flask, rapidly stirring the mixture and heating it to 90° C. for 60 minutes.
[0018] The modified phenolic resin adhesive prepared by the above preparation method is also within the protection scope of the present invention.
[0019] The present invention further proposes the application of the modified phenolic resin adhesive in the preparation of wood resin adhesive.
[0020] Beneficial effects: Compared with the prior art, this application has the following advantages:
[0021] (1) This method aims to simulate the hardening process of lobster epidermis. DCS and PEI@G containing DOPA structure simulate the DOPA derivatives, amino components and inorganic reinforcing agent components in the lobster epidermis, respectively. In the alkaline environment of phenolic resin, DOPA in DCS is oxidized into an o-benzoquinone structure, which covalently crosslinks with the amino groups in PEI@G to form a "phenol-amine" crosslinking network and an organic-inorganic hybrid system, which can achieve simultaneous reinforcement, toughening and rapid curing of phenolic resin.
[0022] (2) This method prepares PEI@G by mixing polyethyleneimine (PEI) and graphite powder in a simple and economical manner and by ball milling. The preparation of PEI@G by the co-mixing ball milling method is simple and environmentally friendly, and can solve the high cost of directly modifying phenolic resin with graphene and the pollution problem of the graphene modification process. In addition, the modification of PEI can promote the uniform dispersion of graphene in the resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the design strategy for DCS / PG / PF phenolic resin;
[0024] Figure 2 Shown are the characterization results of the adhesive in Example 2 and a schematic diagram of the reaction mechanism;
[0025] Figure 3 Shown are the gel properties and mechanical properties characterization results of the adhesives in Examples 1 to 5 and Comparative Examples
[0026] Figure 4 Shown are cross-sectional scanning electron microscope images of wooden boards bonded with adhesives prepared in Example 1, Example 2, Example 4 and the comparative example;
[0027] Figure 5 What is shown is the thermal stability of the adhesive in Example 1, Example 2, Example 4 and the comparative example. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] The present invention provides a method for preparing a phenolic resin adhesive with high toughness, high strength and rapid curing, which is simple, convenient, green and environmentally friendly and has strong industrial feasibility. Inspired by the hardening process of lobster skin, this method combines DCS containing a DOPA structure and PEI@G containing an amino group with a phenolic resin (PF), constructs a "phenol-amine" crosslinking and organic-inorganic hybrid system in the phenolic resin matrix, and prepares a reinforced, toughened and rapid curing phenolic resin DCS / PG / PF. Preparation strategy such as Figure 1 shown.
[0030] Comparative Example 1 Preparation of pure phenolic resin adhesive.
[0031] (1) 50 g of phenol, 40 g of water, 25 g of sodium hydroxide solution (40) and 75 g of formaldehyde solution (36-37 wt%) were mixed in a flask, the mixture was rapidly stirred and heated to 90° C. for 60 minutes, then 22 g of formaldehyde solution (36-37 wt%) and 5 g of sodium hydroxide solution (40 wt%) were kept at 90° C. and rapidly stirred for reaction for 40 minutes, and then the reaction solution was rapidly cooled to 40° C. to obtain a pure phenolic resin adhesive.
[0032] (2) The prepared activated lignin modified phenolic resin adhesive was used to press three-layer poplar plywood, and the performance of the three-layer poplar plywood was tested. The test results are listed in Table 1.
[0033] Comparative Example 2 Preparation of 4% DCS-modified phenolic resin.
[0034] (1) 8 g of chitosan and 8 g of sodium periodate were dispersed in 200 mL of deionized water, and the pH of the reaction system was adjusted to 5 with 0.1 N hydrochloric acid solution. The mixture was kept at 50° C. in the dark for 3 hours, and the reaction product was collected by filtration and washed with water until colorless and then dried to obtain oxidized chitosan (OCS). Oxidized chitosan and 16 g of dopamine were dissolved in anhydrous ethanol, and the reaction system was heated to 80° C. and kept under reflux for 48 hours. After the reaction mixture was dialyzed in water for 3 days, the dialysate was collected by rotary evaporation and freeze-dried to collect DCS.
[0035] (2) Preparation of pure phenolic resin As in the comparative example, 0.8 g DCS and 20 g pure phenolic resin were stirred at room temperature for 20 min to prepare 4% DCS-modified phenolic resin.
[0036] (3) The prepared modified phenolic resin adhesive was used to press three-layer poplar plywood, and the performance of the three-layer poplar plywood was tested. The test results are listed in Table 1.
[0037] Comparative Example 3 Preparation of 4% PEI@G modified phenolic resin.
[0038] (1) 7 g of graphite powder and 35 g of polyethyleneimine were mixed and ball-milled for 20 to 24 hours at a ball-milling speed of 500 rpm. The ball-milled sample was dispersed in water at a concentration of 20 mg / mL and ultrasonicated for 1 hour at an ultrasonic intensity of 400 W. The ultrasonic dispersion was centrifuged for 15 minutes at a centrifugal speed of 3000 rpm, and the upper PEI@G aqueous dispersion was collected and concentrated to a solid concentration of 50% for subsequent preparation of phenolic resin.
[0039] (2) Preparation of pure phenolic resin As in the comparative example, 0.8 g PEI@G and 20 g pure phenolic resin were stirred at room temperature for 20 min to prepare 4% PEI@G modified phenolic resin.
[0040] (3) The prepared modified phenolic resin adhesive was used to press three-layer poplar plywood, and the performance of the three-layer poplar plywood was tested. The test results are listed in Table 1.
[0041] Example 1 Preparation of 4% DCS and PEI@G modified phenolic resin.
[0042] (1) The preparation method of DCS is the same as that in Example 1.
[0043] (2) The preparation method of PEI@G is the same as that in Example 2.
[0044] (3) The preparation method of pure phenolic resin is the same as that in the comparative example.
[0045] (4) 0.4 g DCS and 0.4 g PEI@G were mixed, and the mixture was stirred with 20 g pure phenolic resin at room temperature for 20 min to prepare 4% DCS and PEI@G modified phenolic resin.
[0046] (5) The prepared modified phenolic resin adhesive was used to press three-layer poplar plywood, and the performance of the three-layer poplar plywood was tested. The test results are listed in Table 1.
[0047] Example 2 Preparation of 8% DCS and PEI@G modified phenolic resin.
[0048] (1) The preparation method of DCS is the same as that in Example 1.
[0049] (2) The preparation method of PEI@G is the same as that in Example 2.
[0050] (3) The preparation method of pure phenolic resin is the same as that in the comparative example.
[0051] (4) 0.8 g DCS and 0.8 g PEI@G were mixed, and the mixture was stirred with 20 g pure phenolic resin at room temperature for 20 min to prepare 8% DCS and PEI@G modified phenolic resin.
[0052] (5) The prepared modified phenolic resin adhesive was used to press three-layer poplar plywood, and the performance of the three-layer poplar plywood was tested. The test results are listed in Table 1. Figure 2 Shown are the characterization results and reaction mechanism diagram of the adhesive in Example 2. Figure 2 ac is the X-ray photoelectron spectroscopy (XPS) test result, which is obtained by testing with an AXISSupra XPS instrument equipped with Al Kα X-ray source (1486.6 eV) micro-focused monochromatic light, with a test voltage of 12 kV and a test current of 10 mA; Figure 2 d is the infrared spectrum, which was obtained by Nicolet iS50 infrared spectrometer with a scanning wavelength range of 4000–500 cm -1 .
[0053] Example 3 Preparation of 12% DCS and PEI@G modified phenolic resin.
[0054] (1) The preparation method of DCS is the same as that in Example 1.
[0055] (2) The preparation method of PEI@G is the same as that in Example 2.
[0056] (3) The preparation method of pure phenolic resin is the same as that in the comparative example.
[0057] (4) 1.2 g DCS and 1.2 g PEI@G were mixed, and the mixture was stirred with 20 g pure phenolic resin at room temperature for 20 min to prepare 12% DCS and PEI@G modified phenolic resin.
[0058] (5) The prepared modified phenolic resin adhesive was used to press three-layer poplar plywood, and the performance of the three-layer poplar plywood was tested. The test results are listed in Table 1.
[0059] Among them, the gel time is tested according to the national standard GB / T 14074-2017; the bonding strength is tested according to GB / T 17657-2022 test, poplar veneer was used to prepare plywood, the glue application amount was 125-125g / m2, the plywood was hot pressed at 130℃ and 1MPa pressure for 7 minutes, and after balancing at 25℃ and 50% humidity for 48 hours, it was cut into 100×25×4.5mm3 specimens, and the dry bonding strength was tested by AGS-X-10kN universal tensile testing machine with a tensile rate of 20mm / min. The specimen was boiled in boiling water for 3 hours, and then the wet bonding strength was tested under the above conditions. The adhesion work was calculated by the integral area of the force-displacement curve during the wet bonding strength test; the moisture absorption rate was characterized by the mass change of 100 mesh adhesive powder after balancing at 80% humidity for two days; the water immersion residual rate was characterized by the residual mass of 100 mesh adhesive powder wrapped in filter paper and immersed in 60℃ hot water for 72 hours.
[0060] Table 1 Performance comparison of prepared phenolic resin
[0061]
[0062] According to the national standard GB / T 17657-2022, the glue application amount of poplar veneer is 250-300g / m 2 (double-sided glue coating), hot pressing was performed to prepare three-layer poplar plywood at a temperature of 130°C, a pressure of 1.0 MPa, and a time of 70 s / mm. Figure 3 It can be seen that the gel time, dry glue strength, wet bond strength and toughness of the phenolic resin modified by adding DCS or PEI@G alone are better than those of the pure phenolic resin in the comparative example. The gel time of the modified phenolic resin prepared by adding DCS and PEI@G together is significantly better than that of the unmodified phenolic resin, and the dry glue strength, wet bond strength and toughness are further improved. More obvious fiber damage and fiber pullout can be observed after the bonded section is damaged ( Figure 4 ), indicating that the interaction between the modified phenolic resin and the fiber is stronger. This is because DSC and PEI@G form a "phenolamine" cross-linked network and an organic-inorganic hybrid network with the phenolic resin during curing ( Figure 2 ). In addition, the thermal stability of the modified phenolic resin is also significantly enhanced.
[0063] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a modified phenolic resin adhesive, characterized in that: The steps include: (1) reacting and grafting oxidized chitosan with dopamine to prepare dopamine-grafted chitosan; (2) ball milling polyethyleneimine and graphite powder together to prepare polyethyleneimine functionalized graphene; The DOPA-grafted chitosan obtained in step (1) and the polyethyleneimine-functionalized graphene prepared in step (2) are blended with unmodified phenolic resin to prepare a modified phenolic resin adhesive.
2. The preparation method according to claim 1, characterized in that: In step (1), the oxidized chitosan is prepared by dispersing chitosan and sodium periodate in water, adjusting the system to be acidic and reacting, and then washing the product after the reaction with water until it becomes colorless and drying it.
3. The preparation method according to claim 2, characterized in that: The concentration of chitosan is 8-10wt%, preferably 4wt%, the mass ratio of chitosan to sodium periodate is 1:0.5-1:2, the pH of the reaction system is adjusted to 4.5-5.5 with hydrochloric acid, and the reaction system is placed in a dark environment at 50°C for 3-5 hours.
4. The preparation method according to claim 1, characterized in that: In step (1), oxidized chitosan and dopamine are dissolved in ethanol at a mass ratio of 1:1 to 1:3, the reaction system is heated to 70 to 90°C for 48 to 72 hours, the mixture after the reaction is dialyzed in water for 3 to 5 days, and then rotary evaporated and freeze-dried to obtain dopamine-grafted chitosan.
5. The preparation method according to claim 1, characterized in that: In step (2), graphite powder and polyethyleneimine are mixed in a mass ratio of 1:1 to 1:5 and ball-milled for 20 to 24 hours at a ball-milling speed of 500 to 800 rpm. The ball-milled sample is dispersed in water at a concentration of 10 to 20 mg / mL and ultrasonicated for 1 hour at an ultrasonic intensity of 400 to 500 W. The ultrasonicated dispersion is centrifuged at 3000 to 5000 rpm for 10 to 20 minutes, and the upper PEI@G aqueous dispersion is concentrated to a solid concentration of 50%.
6. The preparation method according to claim 1, characterized in that: In step (3), unmodified phenolic resin is prepared by mixing phenol and formaldehyde in a molar ratio of 1:2.2, and DOPA-grafted chitosan and polyethyleneimine functionalized graphene PEI@G are mixed in a mass ratio of 1:1 and then added to the unmodified phenolic resin for blending. The added mass is 1-12%, and the mixture is stirred at room temperature for 20 minutes to prepare modified phenolic resin DCS / PG / PF.
7. According to claim 6, it is characterized in that: The unmodified phenolic resin was obtained by mixing 50 g of phenol, 40 g of water, 25 g of sodium hydroxide solution and 75 g of formaldehyde solution in a flask, and rapidly stirring the mixture and heating it to 90° C. for 60 minutes.
8. The modified phenolic resin adhesive prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the modified phenolic resin adhesive according to claim 8 in the preparation of wood resin adhesive.
